Assam Third Five Year Plan Vol. 2 1961-66 - Planning Commission (Planning Commission, 1962)
Improvement of Market Intelligence.—The market intelligence will be continued during the Third Plan period also. A sum of Rs. 150 lakhs has been provided in the Third Plan for the purpose.
Assam
Government of Assam